Development of website-based construct 2 interactive multimedia for elementary school students at natural science learning content - Arzita Handayani; Elok Fariha Sari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Limitations in providing innovative learning media can affect learning activities, such as lack of desire to learn and low learning outcomes. Therefore, this research aims to develop website-based construct 2 interactive multimedia products as IPAS learning media on the material of various landscapes and livelihood professions of class IV elementary schools. This research is a type of Reseach and Development research with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used are questionnaires and tests. Validation results from media experts 91.6% and material experts 90% get the category